The discovery and characterization of K‐563, a novel inhibitor of the Keap1/Nrf2 pathway produced by Streptomyces sp - Ran Hori; Kozo Yamaguchi; Hidetaka Sato; Miwa Watanabe; Kyoko Tsutsumi; Susumu Iwamoto; Masayuki Abe; Hideyuki Onodera; Satoshi Nakamura; Ryuichiro Nakai (Cancer Medicine)
Abstract Keap1/Nrf2 pathway regulates the antioxidant stress response, detoxification response, and energy metabolism. Previous reports found that aberrant Keap1/Nrf2 pathway activation due to Kelch‐like ECH‐associated protein 1 (Keap1) mutations or Nuclear factor E2‐related factor 2 (Nrf2) mutations induced resistance of cancer cells to chemotherapy and accelerated cell growth via the supply of nutrients. Therefore, Keap1/Nrf2 pathway activation is associated with a poor prognosis in many cancers. These previous findings suggested that inhibition of Keap1/Nrf2 pathway could be a target for anti‐cancer therapies. To discover a small‐molecule Keap1/Nrf2 pathway inhibitor, we conducted high‐throughput screening in Keap1 mutant human lung cancer A549 cells using a transcriptional reporter assay. Through this screening, we identified the novel Keap1/Nrf2 pathway inhibitor K‐563, which was isolated from actinomycete Streptomyces sp. K‐563 suppressed the expression of Keap1/Nrf2 pathway downstream target genes or the downstream target protein, which induced suppression of GSH production, and activated reactive oxygen species production in A549 cells. K‐563 also inhibited the expression of downstream target genes in other Keap1‐ or Nrf2‐mutated cancer cells. Furthermore, K‐563 exerted anti‐proliferative activities in these mutated cancer cells. These in vitro analyses showed that K‐563 was able to inhibit cell growth in Keap1‐ or Nrf2‐mutated cancer cells by Keap1/Nrf2 pathway inhibition. K‐563 also exerted synergistic combinational effects with lung cancer chemotherapeutic agents. An in vivo study in mice xenotransplanted with A549 cells to further explore the therapeutic potential of K‐563 revealed that it also inhibited Keap1/Nrf2 pathway in lung cancer tumors. K‐563, a novel Keap1/Nrf2 pathway inhibitor, may be a lead compound for development as an anti‐cancer agent.